2012
DOI: 10.1186/1477-7819-10-275
|View full text |Cite
|
Sign up to set email alerts
|

Collagen sealant patch to reduce lymphatic drainage after lymph node dissection

Abstract: BackgroundSeroma formation is a frequent complication following radical lymph node dissection (RLND) in patients with metastatic melanoma. Several strategies have been used to prevent fluid accumulation and thereby reduce the duration of postoperative drainage, including fibrin sealants.MethodsThis was a prospective, single-center study in which consecutive patients undergoing surgical treatment of stage III metastatic melanoma by axillary or ilio-inguinal RLND were randomized to receive standard treatment plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…However, two randomised trials that investigated the use of fibrin sealant in tumour excision and axillary dissection for breast cancer in a total of 190 patients demonstrated a benefit in terms of drain output from the use of fibrin sealant . Di Monta and colleagues showed that the use of fibrin glue in a group of 70 patients undergoing radical lymph node dissection for stage III metastatic melanoma resulted in a significant reduction in duration of drainage …”
Section: Discussionmentioning
confidence: 99%
“…However, two randomised trials that investigated the use of fibrin sealant in tumour excision and axillary dissection for breast cancer in a total of 190 patients demonstrated a benefit in terms of drain output from the use of fibrin sealant . Di Monta and colleagues showed that the use of fibrin glue in a group of 70 patients undergoing radical lymph node dissection for stage III metastatic melanoma resulted in a significant reduction in duration of drainage …”
Section: Discussionmentioning
confidence: 99%
“…Reduction of lymphatic events was not demonstrated in this preliminary reports due to the small number of related events which are probably explained by the relatively low practice and the indiscriminate use of energy to seal lymphatic vessels [8][9][10][11][12][13]. To improve this aspect, we indicate to increase the use of clipping to control small vessels, visualized by laparoscopic magnifi ed vision.…”
Section: Discussionmentioning
confidence: 84%
“…To improve this aspect, we indicate to increase the use of clipping to control small vessels, visualized by laparoscopic magnifi ed vision. As an adjuvant maneuver, biological glue can be used to reduce lymphatic drainage, as demonstrated in other studies of groin dissection [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include closure of dead space [8,9], use of thrombin [10], compression dressings [11,12] aspiration alone instead of drainage [13], use of collagen tissue sealants [14,15], and delaying postoperative shoulder exercises [16]. Use of ultrasonic shears for breast cancer surgery has been described as early as 2000 by Deo et al [17], in which they showed the feasibility of modified radical mastectomy using ultrasonic shears.…”
Section: Discussionmentioning
confidence: 99%